Absence of RET/PTC1 rearrangement in a sample of Colombian individuals with papillary thyroid carcinoma (2019)
Introduction: Papillary thyroid carcinoma is the most common endocrine neoplasm; therefore, markers with possible prognostic utility have been evaluated.Objective: To analyze the presence of RET/PTC1 rearrangement, lymphocytic thyroiditis and associated clinical features in patients with papillary thyroid cancer treated at the Hospital de San José in Bogotá, Colombia.Materials and methods: Clinical records of patients with complete thyroidectomy and diagnosis of papillary cancer were retrospectively identified. RNA was extracted from tumor tissue, and cDNA was obtained using inverse transcriptase to detect the rearrangement of the RET/PTC1 gene by means of qPCR.Results: 55 patients with papillary thyroid cancer were selected; 93% were females, and the mean age was 45.8 years. The most frequent histological variant was classic (49%). A relationship was found between lymphocytic thyroiditis and the number of positive nodes in segments other than central draining, as well as thyroiditis and antithyroid antibody value. No RET/PTC1 rearrangement expression was found.Conclusions: A relationship between lymphocytic thyroiditis and the number of positive nodes in segments other than central draining was found. Other molecular markers should be searched to differentiate the prognosis of these patients.